2021
DOI: 10.3389/frwa.2021.652100
|View full text |Cite
|
Sign up to set email alerts
|

Application of Machine Learning Models to Predict Maximum Event Water Fractions in Streamflow

Abstract: Estimating the maximum event water fraction, at which the event water contribution to streamflow reaches its peak value during a precipitation event, gives insight into runoff generation mechanisms and hydrological response characteristics of a catchment. Stable isotopes of water are ideal tracers for accurate estimation of maximum event water fractions using isotopic hydrograph separation techniques. However, sampling and measuring of stable isotopes of water is laborious, cost intensive, and often not concei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 147 publications
1
4
0
Order By: Relevance
“…16 to 20 mm for Bhavnagar, Gir Somnath and Porbandar while for Dwarka, Junagadh and Jamnagar it was as high as 175 to 219 mm. These findings are also supported by a study by Sahraei et al [40] disclosing that ANN underestimated the events with high maximum values and overestimated the events with low maximum values. Hence, considering all three performance indicators i.e.…”
Section: Admr Based On Ann and Gprsupporting
confidence: 83%
“…16 to 20 mm for Bhavnagar, Gir Somnath and Porbandar while for Dwarka, Junagadh and Jamnagar it was as high as 175 to 219 mm. These findings are also supported by a study by Sahraei et al [40] disclosing that ANN underestimated the events with high maximum values and overestimated the events with low maximum values. Hence, considering all three performance indicators i.e.…”
Section: Admr Based On Ann and Gprsupporting
confidence: 83%
“…The root cause of this behavior may be linked to the training data lacking sufficient extreme samples (Sahraei et al, 2021), impeding the models' ability to adequately learn these patterns. Rahimzad et al, (2021) also support this finding and reported that earlier research, such as (Damavandi et al, 2019;Jimeno-Sáez et al, 2018) has noted similar behavior with models based on neural networks.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies applying deep learning to rainfall-runoff simulation indicate that there is significantly more information in large-scale hydrological data sets than hydrologists have been able to translate into theory or models [129]. GeoAI has also revealed new hydrological patterns and trends, using heterogeneous data from different sources and quality [244,245]. Therefore, novel data-driven modeling provides the potential to gain new information and knowledge and a better understanding of the hydrological system and its changes [129,235].…”
Section: Geoai Capacity To Provide Novel Physical Insightsmentioning
confidence: 99%